A double blind controlled trial of methylprednisolone infusions in systemic lupus erythematosus using individualised outcome assessment. Issue 10 (October 1987) - Edwards, J C; Snaith, M L; Isenberg, D A
Abstract : Twenty one patients with severe systemic lupus erythematosus (SLE) were treated with three daily infusions of either 100 mg or 1 g of methylprednisolone on a randomised double blind basis. Nine patients with unsatisfactory outcome subsequently received the alternative therapy. Patients were rated for improvement on a four point scale using individualised criteria. On three occasions patients improved to 'ideal', on 12 there was 'useful' improvement, on 11 the patient remained static, and on four occasions there was deterioration. There was no significant difference between the clinical states after the two doses. The results suggest that any additional benefit of 1 g of methylprednisolone over 100 mg by repeated infusion in the treatment of active SLE is probably not enough to justify the potential hazards and cost involved.